Everyday inventions: effectively engaging students with human-centred, environmentally sustainable design - Withell, A; Diegel, O; Reay, SD; Charlton, N (AUT University, 2010)
It has become increasingly evident that the impacts of human development and production/consumption over the last half of the twentieth century and into the twenty-first century are unsustainable in the long term. The response to this is an increased focus on identifying opportunities to support and enhance sustainability. „The transition towards sustainability, in its everyday dimension, can be described as follows: in a short period billions of people must redefine their life projects‟ (Manzini & Jegou, 2006). This transition not only presents a huge challenge for product designers but also provides opportunity for designers to begin to reframe their practices and processes. Design education for sustainability can help usher a promising future by transforming the designers of tomorrow (Ramirez, 2006). It is therefore imperative that the teaching of sustainable design thinking is embedded deeply into the curriculum of design programmes. In response to the need for a focus on sustainability in higher education, this paper presents a critical review of a second year product design student project at AUT University, School of Art and Design entitled „Everyday Interventions.‟ This paper will present key aspects of the project including the rationale, approach and processes, as well as student engagement and design outcomes.
Keywords: Sustainable Design; Student engagement